2010
DOI: 10.3324/haematol.2009.013318
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma stem cells: enough evidence to support their existence?

Abstract: Acknowledgments: the authors wish to thank Heber Longas for excellent graphical assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 110 publications
1
38
1
1
Order By: Relevance
“…68,69 Finally, several recent developments have pointed toward the existence of "lymphoid cancer stem cells," which may represent highly desirable targets to achieve a definitive cure in these malignancies. [70][71][72] Although several European groups have already made outstanding contributions to this field, in part within large international consortia, further Section 2. Malignant lymphoid diseases achievements will only be possible if major investments can be realized.…”
Section: The Eha Roadmap For European Hematology Researchmentioning
confidence: 99%
“…68,69 Finally, several recent developments have pointed toward the existence of "lymphoid cancer stem cells," which may represent highly desirable targets to achieve a definitive cure in these malignancies. [70][71][72] Although several European groups have already made outstanding contributions to this field, in part within large international consortia, further Section 2. Malignant lymphoid diseases achievements will only be possible if major investments can be realized.…”
Section: The Eha Roadmap For European Hematology Researchmentioning
confidence: 99%
“…Similar to normal hematopoiesis, leukemia (also known as "blood cancer" characterized by uncontrolled proliferation of blood cells) is caused by leukemia stem cells (LSCs), whose progenitors are capable of self renewal, see Figure 1, [32,41]. There are both acute and chronic versions of the myelogenous and lymphoblastic leukemia (AML, CML, ALL, CLL).…”
Section: Mathematical Model Of Cell Dynamics In Leukemia 21 Biologimentioning
confidence: 99%
“…Since then, many other cancer stem cells (CSCs) have been identified: breast cancer in 2003, brain tumor in 2004, and later, colon, prostate, lung and liver CSCs have followed, [12]. Recently, it has been reported that, in some types of cancers, progenitor cells may become stem cells (this is called plasticity), [27], but for the mathematical model of cell dynamics in leukemia our basis will be Figure 1, which is a simplified version of Figure 1 of [41], where further justifying references can be found.…”
Section: Mathematical Model Of Cell Dynamics In Leukemia 21 Biologimentioning
confidence: 99%
“…Recently, it has been proposed that commited lymphoid progenitors/precursor cells with an active V-D-J recombination program are the initiating cells of follicular lymphoma when targeted by immunoglobulin-gene translocations in the bone marrow. However, these pre-malignant lymphoma initiating cells cannot drive complete malignant transformation, requiring additional cooperating mutations in specific stem cell programs to be converted into the lymphoma originating cells able to generate and sustain lymphoma development [12].…”
Section: The Cell Of Origin Of Follicular Lymphomamentioning
confidence: 99%